Causal associations of thyroid function with inflammatory bowel disease and the mediating role of cytokines - Wu, Shuyun; Yi, Jiazhi; Wu, Bin (Frontiers in Endocrinology, 2024)
Previous observational epidemiological studies have suggested a potential association between thyroid function and inflammatory bowel disease (IBD).However, the findings remain inconclusive, and whether this association is causal remains uncertain. The objective of this study is to investigate the causal association between thyroid function and IBD.Genome-wide association studies (GWAS) involving seven indicators of thyroid function, IBD, and 41 cytokines were analyzed. Bidirectional two-sample Mendelian randomization (MR) and multivariable MR were conducted to examine the causal relationship between thyroid function and IBD and to explore the potential mechanisms underlying the associations.Genetically determined hypothyroidism significantly reduced the risk of CD (odds ratio [OR] = 0.761, 95% CI: 0.655-0.882, p < 0.001). Genetically determined reference-range TSH was found to have a suggestive causal effect on IBD (OR = 0.931, 95% CI: 0.888-0.976, p = 0.003), (Crohn disease) CD (OR = 0.915, 95% CI: 0.857-0.977, p = 0.008), and ulcerative colitis (UC) (OR =0.910, 95% CI: 0.830-0.997, p = 0.043). In reverse MR analysis, both IBD and CD appeared to have a suggestive causal effect on the fT3/fT4 ratio (OR = 1.002, p = 0.013 and OR = 1.001, p = 0.015, respectively). Among 41 cytokines, hypothyroidism had a significant impact on interferon-inducible protein-10 (IP-10) (OR = 1.465, 95% CI: 1.094-1.962, p = 0.010).The results of multivariable MR showed that IP-10 may mediate the causal effects of hypothyroidism with CD.Our results suggest that an elevated TSH level reduces the risk of CD, with IP10 potentially mediating this association. This highlights the pituitary-thyroid axis could serve as a potential therapeutic strategy for CD.